Strategi Internalisasi Nilai-nilai Religius PAI dalam Mengembangkan Religiusitas Siswa di SMA NW Suralaga - Muhammad Misnur Efendi; Mohamad Iwan Fitriani (MANAZHIM, 2023)
Current technological advances do not rule out the possibility of eliminating religious values ​​in the younger generation, especially at the high school level because information is spreading very quickly, both from within and outside the country, to keep the younger generation from being carried away by the negative impacts of technology, educators is expected to help students through a good strategy to develop student religiosity.The purpose of this study was to explain the strategy of internalizing the religious values ​​of PAI in SMA NW Suralaga.This research uses qualitative research. So the results obtained are descriptive results or exposure of an event under study. In connection with this, in this study the researchers used several data collection methods such as observation, interviews and documentation, while the data analysis used the Miles and Huberman model analysis in reducing the data so that the data became systematic and logical.This study resulted in the findings that: In internalizing religious values ​​in PAI learning the teacher must have a strategy so that the values ​​to be internalized can be successful, the strategy for internalizing religious values ​​at SMA NW Suralaga is a strategy of exemplary, Ibrah and Amtsal, giving advice, habituation, and discipline.